2016
DOI: 10.1016/j.jpainsymman.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in a Subset of Breast Cancer Patients After Systemic Therapy—Results From a Longitudinal Study

Abstract: Our findings indicate that cognitive impairment after systemic treatment occurs in a subset of BC patients. The predictive value of demographic and psychosocial factors in cognitive impairment should be further investigated in a larger sample of impaired patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 37 publications
1
67
2
Order By: Relevance
“…As our fMRI tasks were only partly sensitive to group differences, future studies should employ fMRI paradigms that allow for detection of subtle differences in BOLD signal, as well as performance. Although the sample size of the current study was larger than previous longitudinal studies, our neuropsychological analyses showed that cognitive decline ‘only’ occurred in 16% patients who received systemic treatment [16]. This percentage is arguably too low to detect differences at the group level.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As our fMRI tasks were only partly sensitive to group differences, future studies should employ fMRI paradigms that allow for detection of subtle differences in BOLD signal, as well as performance. Although the sample size of the current study was larger than previous longitudinal studies, our neuropsychological analyses showed that cognitive decline ‘only’ occurred in 16% patients who received systemic treatment [16]. This percentage is arguably too low to detect differences at the group level.…”
Section: Discussionmentioning
confidence: 62%
“…The current report will focus on longitudinal analyses of task-related functional MRI. Analyses of neuropsychological performance are described in [16]. Findings for other MRI modalities will be described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Patients' ages varied. To avoid age‐related cognitive impairment, nine studies selected patients younger than 75 . Three studies specifically targeted elders .…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these reported significantly different longitudinal changes between the CTX group and controls, with the CTX group experiencing more impairment after initiating chemotherapy than controls . Two publications from the same data set reported higher levels of SCI in the CTX group than controls after initiating chemotherapy (see Table for differences). All of these findings supported the impact of chemotherapy on SCI.…”
Section: Resultsmentioning
confidence: 99%
“…Several longitudinal studies 6,10,11,[17][18][19][20][21][22] examined factors associated with cognitive decline or cognitive change, after initiating chemotherapy. Yet, results need to be replicated due to contradictory outcomes, small sample sizes, and the inclusion of limited numbers of possible risk factors.…”
mentioning
confidence: 99%